2010
DOI: 10.3851/imp1612
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Abnormal Liver Stiffness in HIV-infected Patients without Viral Hepatitis Coinfection: Role of Didanosine

Abstract: The prevalence of abnormal LS in HIV-infected patients without HBV or HCV coinfection is substantial. Long-term exposure to ddI is a major cause of liver damage in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 43 publications
4
64
2
Order By: Relevance
“…Beside we have not analyzed the impact of different antiretroviral drugs on transient elastography measures. More elevated transient elastography measures caused by antiretroviral drugs, due to liver toxicity or steatosis, could imply a higher proportion of false-positive cases [29,30].…”
Section: Discussionmentioning
confidence: 97%
“…Beside we have not analyzed the impact of different antiretroviral drugs on transient elastography measures. More elevated transient elastography measures caused by antiretroviral drugs, due to liver toxicity or steatosis, could imply a higher proportion of false-positive cases [29,30].…”
Section: Discussionmentioning
confidence: 97%
“…We selected as cases all patients fulfilling criteria of abnormal LS of uncertain origin as previously described among those who attended both institutions. 11,12 Briefly, we selected HIV-infected patients with a LS ≥ 7.2 kiloPascals (kPa) in two consecutive visits, without previous exposure to HBV or HCV as determined by a negative hepatitis B surface antigen, negative HCV antibodies and a negative serum DNA HBV and RNA HCV PCR assessment, and without evidence of other causes of liver disease. Forty-four patients fulfilled these criteria before 30th June 2011.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…[8][9][10] Unexplained elevations of liver stiffness (LS) were found in 11% of the HIV-infected patients without hepatitis B virus (HBV) or hepatitis C virus (HCV) co-infection from our cohort. 11 Liver histology proved several sort of liver damage virtually in all patients with unexplained elevations of LS. 11 In those with normal values of LS, sequential examinations revealed that 7% of them developed persistent elevations of LS, which were mainly attributed to fatty liver disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This progression is not linear over time and may occur after only a few years [1,2]. Significant fibrosis in this setting has been linked to a low CD4 cell count, a longer estimated duration of HCV infection, daily alcohol intake, a higher necroinflammation score, steatosis, uncontrolled HIV replication, late initiation of antiretroviral therapy, mitochondrial toxicity due to antiretroviral drugs such as didanosine and insulin resistance (IR) [3][4][5][6][7]. The risk of hepatocellular carcinoma (HCC) is two to six times higher in HIV/HCV-co-infected patients than in HCVmono-infected patients [8].…”
Section: Introductionmentioning
confidence: 99%